Genetic Variability among growth and seed yield attributes of Jatropha curcas (L.) - Kumar, Sudhir; Pandey, S.K.; Ranjan, Rajeev; Dhyani, S.K.; Kumar, R.V.; Ahlawat, S.P. (Indian Journal of Agroforestry, 2020)
Twelve accessions of Jatropha curcas collected from three states were grown in randomized block design and evaluated for growth and yield characters. Findings revealed significant differences (p>0.5% and 0.1% level) among all the accessions for their growth parameters. Significant positive correlations (r =0.388 to 0.955, p<0.01 level) were observed between all the traits (plant height, collar diameter, number of primary and secondary branches, branch length and canopy diameter) with each other. The seed yield varied from minimum of 32.5 g/plant in NRCJ-50 to maximum of 470g/plant in NRCJ-92. This was followed by NRCJ-41 (310g) and NRCJ-40 (290g). Average seed yield was 160.38 g/ plant. The variation found in different traits can be effectively utilized in genetic improvement of this species.